Effects of feeding regimes on phenotype and performance in Atlantic salmon - Persson, Lo (2017)
Atlantic salmon populations have declined worldwide across their distribution. This is partly due to hydro power development that has degraded freshwater habitat and cut off the migration routes between the freshwater habitat and the sea. To prevent extinctions, and to compensate fisheries for decreased natural production, supplementary rearing and releases of hatchery-reared fish are common. However, the survival of released hatchery-reared fish has been lower compared to wild fish, and since the middle 1990s the survival has decreased even more. The decrease in survival coincides with a large increase in smolt size and an increasingly deviant phenotype compared to wild smolts. In this thesis I examine how different feeding regimes used in the hatchery can affect the size and the energetic state of hatchery-reared salmon. I test the effects of a more wild-like phenotype on downstream migration as smolts and monitor their adult return rates from the sea. Large scale feeding experiments were done in a hatchery environment and smaller scale experiments were done in an adjacent research laboratory. Different marking techniques such as passive integrated transponder (PIT)-, and acoustic tags, were used to monitor fish movement and adult return rates. By using restricted feed rations and periods of starvation, phenotypically wild-like smolts, in terms of body size and energetic state, could be produced. Fish with strongly restricted feed rations suffered from severe dorsal fin damage and higher mortality. Moderate feed restrictions did not affect fin damage nor mortality. Lower energetic state increased the migration speed in experimental streams. In the river, lower energetic state and increased smolt length increased the sea entry. However, the most important factor for successful sea entry was the discharge in the river. Modelling of individual smolt characteristics showed that smolts of intermediate size had the highest probability of adult return from the sea. My results suggest that in order to have the highest ...